Identifying Motivational Factors in Nahwu Courses Using Principal Component Analysis (Pca): A Study of Arabic Language Education Students - Khairani, Annisa Raina; Fikri, Shofil; Syaqifah, Iklil; Juliansyah, Iqbal; Syalsabila, Annisa (Abjadia : International Journal of Education, 2026)
The challenges faced by students in studying Nahwu, an essential component of the Arabic language, often relate to the complexity of its rules, making it feel difficult and diminishing learning motivation. This study aims to analyze the factors influencing students' learning motivation in Nahwu courses at the university level, offering solutions through a deeper understanding of intrinsic motivation, extrinsic motivation, and amotivation. The research employed a descriptive quantitative method with factor analysis using Principal Component Analysis (PCA). Data were collected over a one-month period via questionnaires from 46 fifth-semester students (cohort 2020) in the Arabic Language Education Program at UIN Datokarama Palu. The motivation indicators employed in this study were based on the Academic Motivation Scale (AMS) developed by Robert J. Vallerand, which comprises seven distinct indicators. The findings reveal two main factors affecting learning motivation: the Self-Regulation Factor, which is associated with positive motivation, and the Helplessness Factor, reflecting feelings of inability. These findings are expected to provide insights for educators in creating effective teaching methods to enhance students' motivation and learning outcomes in Nahwu courses.